Product Development and International Trade - Grossman, Gene M.; Helpman, Elhanan (Journal of Political Economy, 1989)
We develop a multicountry, dynamic general equilibrium model of product innovation and international trade to study the creation of comparative advantage through research and development and the evolution of world trade over time. In our model, firms must incur resource costs to introduce new products, and forward-looking potential producers conduct R & D and enter the product market whenever profit opportunities exist. Trade has both intraindustry and interindustry components, and the different incentives that face agents in different countries for investment and savings decisions give rise to intertemporal trade. We derive results on the dynamics of trade patterns and trade volume and on the temporal emergence of multinational corporations.